'Lepidotes' crassus Nicolet, 1872 - comments on a forgotten species, as well as transcription, translation and facsimile of the original description - Leuzinger, Léa Sylvia (2021)
Coincidentally, we stumbled across the description of a forgotten fossil fish from the Swiss Jura. All so far known details about the species ¨Lepidotes¨ crassus Nicolet, 1872, have been gathered. Together with a transcription of the original text in French, a translation to English, and graphically treated versions of the original figures, we also provide a facsimile of Nicolet`s text from the journal Le Rameau de Sapin.